Molecular modeling of the interaction of Ilmofosine as a therapeutic agent against Trypanosoma cruzi amastigotes in the treatment of Chagas disease - Granizo Doumet, Gustavo Adib (2024)
This study investigates the efficacy of ilmofosine and ketoconazole, both individually and in combination, against Trypanosoma cruzi amastigotes, the causative agent of Chagas disease. The research encompasses both experimental and computational approaches. In vitro experiments were conducted using Vero cell cultures infected with T. cruzi blood trypomastigotes, which later developed into amastigotes. Various concentrations of ilmofosine and ketoconazole were tested separately to determine their inhibitory effects on parasite replication and the results demonstrated a drug concentration-dependent reduction in amastigote numbers, with complete eradication observed at 1 μM of ilmofosine and 4 nM of ketoconazole. Furthermore, the combined treatment exhibited a synergistic effect, totally inhibiting at a lower concentration the parasite replication in Vero cell cultures using 0.2 μM of ilmofosine and 2 nM of ketoconazole. In addition to the experimental work, molecular modeling and docking simulations were employed to elucidate the interactions between these drugs and the metabolic pathways essential for the replication of T. cruzi. Ilmofosine demonstrated inhibitory activity on phosphatidylethanolamine N-methyltransferase (PEMT) of the Bremer-Greenberg transmethylation pathway, while ketoconazole showed an inhibitory effect on sterol 14α-demethylase (CYP51) and sterol 24-C-methyltransferase of the ergosterol biosynthesis pathway. The docking studies revealed that the combination of ilmofosine and ketoconazole exerted an inhibitory and synergistic effect on these enzymes. The integration of experimental data with computational modeling offers a comprehensive understanding of the therapeutic potential of ketoconazole and ilmofosine in combination against T. cruzi and contributes to the development of more effective treatment strategies for Chagas disease.